2020
DOI: 10.3390/foods9040399
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Consumers Choice of Healthier Foods: A Comparison of Different Front-of-Package Labelling Schemes Using Slovenian Food Supply Database

Abstract: Summary indicator front-of-package nutrition labelling schemes are gaining momentum. In Europe, an example of such a scheme is Nutri-Score, which was first introduced in France. Supported by additional research, the scheme has the potential to expand into other countries. Such a scenario opens a series of questions related to the use of Nutri-Score in the territories with pre-existing food labelling schemes. A key question is whether different nutrition labelling schemes would provide conflicting information f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…The reported differences in nutrient profiling approaches of different labelling schemes highlight areas that need to be carefully addressed during the harmonisation of FOPNL in Europe. Consistency among labelling profiles is vital in order to provide unambiguous information to consumers [50,51]. For example, the NS for fats and cheeses is mentioned as being of concern in some countries, and some countries point out inconsistencies with their national recommendations [28,52].…”
Section: Discussionmentioning
confidence: 99%
“…The reported differences in nutrient profiling approaches of different labelling schemes highlight areas that need to be carefully addressed during the harmonisation of FOPNL in Europe. Consistency among labelling profiles is vital in order to provide unambiguous information to consumers [50,51]. For example, the NS for fats and cheeses is mentioned as being of concern in some countries, and some countries point out inconsistencies with their national recommendations [28,52].…”
Section: Discussionmentioning
confidence: 99%
“…However, the same method is commonly used to compare two different nutrient profile models in order to determine the suitability or reliability of the nutrient profile model used with other nutrient profile models as a reference. This was demonstrated in other studies comparing models of varied nutrient profile with different types of food (Pivk Kupirovič et al 2020;Labonté et al 2017). This comparison can help regulators to determine the nutrient profile model to be used as a reference (Poon et al 2018).…”
Section: Comparison Of Sodium Threshold Bymentioning
confidence: 70%
“…Products exhibiting a mandated labelling such as the HSR enhance consumers' capacity to identify and choose healthier food items even if they did not view the BOP nutrition information. In addition, a recent study conducted by Kupirovic et al showed that all front-of-package nutrition labelling systems will make it easier for customers to make healthier decisions so they can follow dietary recommendations and distinguish within a category between healthy and less healthy items [49]. The limitations for nutrient profiling include not enough evidence as to which labelling scheme is most suitable and successful.…”
Section: Discussionmentioning
confidence: 99%